Microstructural Characterization of Aluminum-Carbon Nanotube Nanocomposites Produced Using Different Dispersion Methods. (8th March 2016) - Simões, Sónia; Viana, Filomena; Reis, Marcos A. L.; Vieira, Manuel F.
Abstract: This research focuses on characterization of the impact of dispersion methods on aluminum-carbon nanotubes (Al-CNTs) nanocomposite structure. Nanocomposites were produced by a conventional powder metallurgy process after the dispersion of the CNTs on the Al powders, using two approaches: (1) the dispersion of CNTs and mixture with Al powders were performed in a single step by ultrasonication; and (2) the CNTs were previously untangled by ultrasonication and then mixed with Al powders by ball milling. Microstructural characterization of Al-CNT nanocomposites was performed by optical microscopy, scanning and transmission electron microscopy, electron backscatter diffraction, and high-resolution transmission electron microscopy (HRTEM). Microstructural characterization revealed that the use of ball milling for mixing CNTs with Al powders promoted the formation of CNT clusters of reduced size, more uniformly dispersed in the matrix, and a nanocomposite of smaller grain size. However, the results of HRTEM and Raman spectroscopy show that ball milling causes higher damage to the CNT structure. The strengthening effect of the CNT is attested by the increase in hardness and tensile strength of the nanocomposites.